Strategic Interplay in Times of Crisis. Opportunities and challenges for state-civil society interaction during the Swedish "Refugee Crisis" of 2015–2016 - Jämte, Jan; Pitti, Ilaria (PARTECIPAZIONE E CONFLITTO, 2019)
From mid-2015 to early 2016, more than a million refugees and migrants arrived in Europe, after having crossed the Mediterranean Sea. Sweden quickly emerged as one of the main destinations they aspired to reach. During the so-called refugee crisis of 2015–2016, the city of Malmö became the management center for the reception of refugees. In this context, a series of interplays emerged between governmental institutions (GIs), non-governmental organizations (NGOs), and social movement organizations (SMOs) involved in helping the refugees. Looking at the refugee crisis in Malmö through the lens of an interactionist approach to contentious politics, this article analyzes the strategic interplay between SMOs, NGOs, and GIs in the different phases of the crisis, as well as scrutinizes the conditions that facilitated or hindered cooperation among the actors. Results show that the crisis initially strengthened the role of SMOs, but that in order to enter into lasting and established forms of cooperation with NGOs and institutionalized politics, SMOs had to meet three conditions: 1) have a clear organizational structure, 2) downplay their political ideology, and 3) assume a complementary position to the other actors involved. For most SMOs, this limited their maneuverability, leading them to adopt one of three possible strategies: adapting to the new conditions, challenging the rules and players of the arena, or exiting the arena altogether.